Relaciones interpersonales y clima organizacional entre el personal administrativo, Empresa de Transportes Nuevo California S.A., Víctor Larco, 2021 - Castillo Miñano, Claudia Jennifer (2023)
This study seeks to analyze the influence of interpersonal relationships on the organizational climate among administrative staff, Empresa de Transportes Nuevo California S.A., Víctor Larco, 2021. The population for the present investigation were 63 members of the administrative staff, whose ages range from 22-57 years, whose highest percentage are male. In the present investigation three methods are applied: Inductive - Deductive, Synthetic Analytical, Statistical; Research techniques such as interview, observation and survey were also used, and instruments such as interview guide, interview record, observation guide, observation record and questionnaire, which allowed obtaining quantitative and qualitative data allowing the analysis of the indicators. and variables. The results obtained from the investigation were statistically represented in a negative way in the organizational climate, evidencing the lack of work motivation and poor communication between administrative staff.